Pengembangan Potensi Diri Generasi Muda di Indonesia dengan Cipta, Rasa, dan Karsa (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
The aim of this research is to determine the form of developing students' self-potential through the educational process. This is motivated by the varying levels of students' self-potential in this school, some teachers understand and understand how to develop students' self-potential, but some teachers do not yet understand it, so that students' self-potential is formed by itself. However, the school has already developed students' potential. Therefore, researchers conducted research to analyze what form of development of students' personal potential was carried out by teachers at the school. This type of research uses a qualitative approach, with data collection techniques using observation, interviews and documentation. Then analyze the data using triangulation. Based on the research results, it is known that the form of developing students' self-potential carried out by teachers is providing intensive guidance for students, providing assistance for students who have less interest and motivation to learn, providing good role models, inviting students together. by cleaning the school environment, carrying out congregational Duha prayers every Friday morning, conducting tests on new students, holding extracurricular activities, and giving sanctions and warnings to students. Then the challenge for teachers in developing students' potential is the students' attitudes, interests and motivation, teacher competence, school facilities and infrastructure, and the environment around the students.